2021
DOI: 10.1186/s12889-021-11956-6
|View full text |Cite
|
Sign up to set email alerts
|

Youth susceptibility to tobacco use: is it general or specific?

Abstract: Background Susceptibility to tobacco use predicts tobacco use onset among youth. The current study aimed to estimate the extent of overlap in susceptibilities across various tobacco products, investigate sociopsychological correlates with susceptibilities, and examine whether the relationship linking susceptibility with the onset of use is product-specific or is accounted for by a general susceptibility-onset relationship. Methods The study populat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Third, we assessed susceptibility using only one question that was focused on use in the upcoming year. However, prior work has suggested that including additional questions related to curiosity and the likelihood of use if a friend offered the product may more fully represent the construct of susceptibility [ 12 , 21 ]. Fourth, young adults who currently used tobacco products were over-represented in our analytic sample based on the quota-based sampling we employed for the parent study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we assessed susceptibility using only one question that was focused on use in the upcoming year. However, prior work has suggested that including additional questions related to curiosity and the likelihood of use if a friend offered the product may more fully represent the construct of susceptibility [ 12 , 21 ]. Fourth, young adults who currently used tobacco products were over-represented in our analytic sample based on the quota-based sampling we employed for the parent study.…”
Section: Discussionmentioning
confidence: 99%
“…While we could not directly assess the impact of the term “tobacco-free” in the current study, future research is needed to establish the impact of this term on product perceptions, susceptibility, and use of NPs. Eighth, it is not clear the extent to which the correlates of NP susceptibility and use are unique to NPs or would generalize to smokeless tobacco, and future research is needed on this topic [ 21 ]. Finally, it is possible that NP susceptibility and use may be beneficial for young adults who are using higher-risk tobacco products (e.g., cigarettes, smokeless tobacco) and wish to switch to exclusive NP use as a means of harm reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility measures have been developed to help predict which youth are most likely to initiate ENDS use. The Pierce measure ( Pierce et al, 1996 ) was initially developed to forecast cigarette smoking but has been adapted in various forms to predict initiation of ENDS ( Strong et al, 2015 , Bold et al, 2017 , Cheng et al, 2021 ). In this study we account for this measure of susceptibility and other variables associated with likelihood of ENDS initiation and sleep quality, including parental education ( Vu et al, 2020 ), household income ( Patel et al, (2021 ), availability of tobacco products in the home ( Bailey et al, 2022 ; ( Bouchard et al, 2018 ), prior use of tobacco, alcohol, and illicit substances ( Brake, 2019 ), school performance ( Nicksic and Barnes, 2019 ), experiences with anxiety and depression ( Green et al, 2018 , Jamieson et al, 2020 ), perceptions of ENDs harmfulness ( Tackett et al, 2021 , Strong et al, 2019 ), sensation seeking ( Case et al, 2017 , Carey et al, 2019 ), having friends that use ENDS ( Groom et al, 2021 ), exposure to ENDS promotions on social media ( Holtz et al, 2021 ), Body Mass Index (BMI) ( Moore et al, 2011 ) and physical activity ( Youngstedt, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…The questions youth respondents were asked include: “Have you ever been curious about using an electronic nicotine product?,” “Do you think you will try an electronic cigarette or e-cigarette soon?,” “Do you think you will use an e-cigarette in the next year?,” and “If one of your best friends were to offer you an electronic cigarette or e-cigarette, would you use it?” Answer choices for the first question include, “ Not at all curious, ” “ A little curious, ” “ Somewhat curious, ” or “ Very curious. ” Answer choices to the other three questions include, “ Definitely yes,” “Probably yes,” “Probably not,” and “ Definitely not.” To define ENDS susceptibility, we follow Cheng et al (2021) , who calculated susceptibility as any answer other than “ Not at all curious ” to the first question and “ Definitely not ” to the other three questions. We created a dummy variable for susceptibility where 1 represented a respondent who was considered susceptible to ENDS initiation and 0 represented a respondent who was not.…”
Section: Methodsmentioning
confidence: 99%
“…These cross-national variations caution against relying solely on "one size fits all" intervention strategies (Chassin et al 2014) The result study from Kinga Polanska, Malgorzata Znyk, Dorota Kaleta: the following factors were not significant correlates of tobacco use susceptibility in any of the analyzed countries: parental education, age of the students, parental smoking, exposure to passive smoking at home, presence of the smokers inside school or outside school on school property, knowledge about harmful effects of active smoking, perception of difficulty of quitting by smokers and school discussion of the reasons why people use tobacco (p > 0.05) (Polanska et al 2022) The literature has shown the social factors, and those related to educational and policy issues as well as to attitudes regarding tobacco use were strongly, and consistently across countries, correlated with tobacco use susceptibility. Slight differences in susceptibility to tobacco use between the countries were related to: sex, money available for own expenses, exposure to advertisements or promotions at points of sale and opinion that people who smoke have more friends (Polanska et al 2022) Hui G. Cheng, et al (2021) describes adolescents' susceptibility to tobacco use. The results of the study explain that 65% of adolescents who consume one tobacco product are susceptible to consuming more than one tobacco product.…”
Section: Literature Reviewmentioning
confidence: 99%